Influence of In Vitro IL-2 or IL-15 Alone or in Combination with Hsp-70-Derived 14-mer Peptide (TKD) on the Expression of NK Cell Activatory and Inhibitory Receptors - Ilona Hromadnikova; Petra Pirkova; Lucie Sedlackova (Mediators of Inflammation)
NK cells represent a potential tool for adoptive immunotherapy against tumors. Membrane-bound Hsp70 acts as a tumor-specific marker enhancing NK cell activity. Using flow cytometry the effect of in vitro stimulation with IL-2 or IL-15 alone or in combination with Hsp70-derived 14-mer peptide (TKD) on cell surface expression of NK activatory receptors (CD16, NKG2D, NKG2C, NKp46, NKp44, NKp30, KIR2DL4, DNAM-1, and LAMP1) and NK inhibitory receptors (NKG2A, KIR2DL2/L3, LIR1/ILT-2, and NKR-P1A) in healthy individuals was studied. Results were expressed as the percentage of receptor expressing cells and the amount of receptor expressed by CD3−CD56+ cellular population. CD94, NKG2D, NKp44, NKp30, KIR2DL4, DNAM-1, LAMP1, NKG2A, and NKR-P1A were upregulated after the stimulation with IL-2 or IL-15 alone or in combination with TKD. KIR2DL2/L3 was upregulated only by IL-15 and IL-15/TKD. Concurrently, an increase in a number of NK cells positive for CD94, NKp44, NKp30, KIR2DL4, and LAMP1 was observed. IL-15 and IL-15/TKD caused also cell number rise positive for KIR2DL2/L3 and NKR-P1A. Cell number positive for NKG2C and NKG2A was increased only by IL-2 and IL-2/TKD. The diverse effect of IL-2 or IL-15 w or w/o TKD on cell surface expression was observed in CD16, NKp46, and LIR1/ILT-2.